How to Build a Winning Climate in Academic Support Services - McElroy, Lee E. (My University, 1985)
The author describes the importance of organizational climate in an academic support services unit for athletes. It has five components: commitment, enthusiasm, vision, values, and structure.
Keywords: work environment